Effects of hydrolyzed vegetable protein or hydrolyzed vegetable and meat protein blend on nursery pig performance from 15 to 40 lb - Marcio Antonio Dornelles Goncalves; Joel M DeRouchey; Steven S Dritz; Michael D Tokach; Robert D Goodband; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 280 pigs (PIC 327 × 1050, initially 16.7 lb BW) were used in a 28-d trial to evaluate the effects of hydrolyzed vegetable protein or a blend of hydrolyzed vegetable and meat protein for nursery pigs. Three days after weaning, pigs were allotted to 1 of 4 dietary treatments in a completely randomized design, balancing for initial BW and gender. There were 10 pens per treatment with 7 pigs per pen. The 4 treatment diets were: (1) no added specialty protein source (negative control); (2) 6% select menhaden fish meal; (3) 5% hydrolyzed vegetable protein (Hydr SF 52, International Ingredient Corporation, St. Louis, MO), or (4) 6.5% hydrolyzed vegetable and meat protein blend (HDSF Protein; International Ingredient Corporation). Diets were fed in 2 phases, with Phase 1 from d 0 to 17 (treatment diets) and Phase 2 from d 17 to 28 (common diet). From d 0 to 17, pigs fed the negative control diet had improved (P â‰¤ 0.05) F/G compared with pigs fed diets with Hydr SF 52 or HDSF Protein. No differences in ADG and ADFI were detected among treatments. From d 17 to 28 (common period), no difference was observed in growth performance between pigs previously fed any of the treatment diets. Overall (d 0 to 28), no differences were observed in ADG, ADFI, or F/G among pigs fed any of the treatment diets. Because performance did not differ from pigs fed the negative control diet, definitive conclusions regarding these specialty protein sources cannot be made.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Hydrolyzed vegetable protein; Meat protein; Protein sources; Nursery pig